2006
DOI: 10.1111/j.1440-1797.2006.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of leflunomide in the treatment of immunoglobulin A nephropathy

Abstract: These preliminary results are encouraging, but further randomised studies are required before leflunomide can be recommended for the treatment of IgA nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
1
33
1
Order By: Relevance
“…However, nephrotic syndrome reappeared in five out of the 23 patients (21.7%) who were in remission by 15 months. Median time to relapse was 14 months (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] after cessation of LEF. There were no significant differences in either biochemical or demographic parameters at baseline between relapsing and non-relapsing patients.…”
Section: Relapse and Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nephrotic syndrome reappeared in five out of the 23 patients (21.7%) who were in remission by 15 months. Median time to relapse was 14 months (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] after cessation of LEF. There were no significant differences in either biochemical or demographic parameters at baseline between relapsing and non-relapsing patients.…”
Section: Relapse and Renal Functionmentioning
confidence: 99%
“…Yu et al 19 reported that LEF significantly reduced proteinuria in 77.7% patients with refractory nephrotic syndrome. Lou et al 20 reported a response rate of 72.4% after 7 months of LEF treatment in immunoglobulin A nephropathy patients in a randomized controlled trial. These clinical observations indicated that LEF may have potential therapeutic effect on glomerular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In two comparison trials, researchers also found that leflunomide induced complete remission and decreased proteinuria and Scr in patients with IgA nephropathy 39,40 . Adverse events were mild in each trial.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to previous studies, our study also found that patients treated with combination therapy (valsartan with clopidogrel and leflunomide) as a treatment for progressive IgA nephropathy were safe and effective. However, Lou et al also observed a greater rate of deterioration (renal function decline and proteinuria increase >30%) with leflunomide versus ACE inhibitors 39 . Therefore, although these preliminary results are encouraging and leflunomide appears to be a promising treatment, there are limited data supporting the use of Leflunomide as an investigational therapy for progressive IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing incidence and poor outcome of IgAN result in a large expenditure of healthcare resources and a significant burden for patients and society. In terms of immunosuppressive therapy, medications including glucocorticoids, cyclophosphamide (CTX), leflunomide (LEF), cyclosporine A (CsA), and mycophenolate mofetil (MMF), have been used in IgAN treatment (5)(6)(7)(8)(9). Despite the clinical efficacy of these therapies, many patients do not acquire clinically meaningful remission or they discontinue treatment because of various adverse events.…”
Section: Introductionmentioning
confidence: 99%